Mathematical Modeling of Moisture Sorption Isotherms and Determination of Isosteric Heats of Sorption of Ziziphus Leaves - Amel Saad; Boumediene Touati; Belkacem Draoui; Boufeldja Tabti; Asma Abdenebi; Said Benaceur (Modelling and Simulation in Engineering)
Desorption and adsorption equilibrium moisture isotherms of Ziziphus spina-christi leaves were determined using the gravimetric-static method at 30, 40, and 50°C for water activity (aw) ranging from 0.057 to 0.898. At a given aw, the results show that the moisture content decreases with increasing temperature. A hysteresis effect was observed. The experimental data of sorption were fitted by eight models (GAB, BET, Henderson-Thompson, modified-Chung Pfost, Halsey, Oswin, Peleg, and Adam and Shove). After evaluating the models according to several criteria, the Peleg and Oswin models were found to be the most suitable for describing the sorption curves. The net isosteric heats of desorption and adsorption of Ziziphus spina-christi leaves were calculated by applying the Clausius-Clapeyron equation to the sorption isotherms and an expression for predicting these thermodynamic properties was given.